The dire days of Willowweep manor - Garrity, Shaenon K. (Margaret K. McElderry Books, 2021)
After she saves a man from drowning, Haley wakes up in a pocket universe that appears as a gothic estate and helps three brothers whose job it is to protect her world against a penultimate evil.